Hospitalization for cancer among radiologists in Taiwan - Wang, Yi-Fen; Hung, Chin-Tun; Li, Shu-Fen; Lee, Mei-Wen (La Medicina del Lavoro, 2015)
Background: Population aging and the incremental use of high-tech instruments increase the demand for radiological examinations and treatments in medical services. The exposure of radiologists and other medical workers to medical treatment radiation may thus be increased. Objectives: The aim of the study was to explore the average number of cancer hospitalizations and use of hospitalization as cancer treatment for radiologists compared with that for family medicine physicians, as well as the trends in the annual average number of cancer hospitalizations among radiologists. Methods: Research data were obtained from the 2000-2010 Taiwan National Health Insurance Research Database. These samples collected for this study were unbalanced panel data. Results: The average number of cancer hospitalizations for radiologists from 2000 to 2010 ranged between 3.67 and 28.26‰. After controlling the effects of gender, age, hospital accreditation level and year using generalized estimating equations with a binomial distribution and logit link function, our study found that radiologists had non significant higher risk of cancer hospitalizations compared with family medicine physicians. However, the average number of cancer hospitalizations for radiologists showed an annual decline from 2000 to 2010. Conclusions: Compared with family medicine physicians, radiologists had non significant higher risk of cancer hospitalizations. The data period examined in this study was only 11 years. Considering the numerous new radiological procedures currently in use in modern medical treatments, the health status of medical radiation workers should be continuously monitored in the future.